Experimental study of a compact unglazed Solar Thermal Facade (STF) for energy-efficient buildings - Shen, Jingchun; Zhang, Xingxing; Yang, Tong; Tang, Llewellyn; Shinohara, Hiroyuki; Wu, Yupeng; Wang, Hong; Pan, Song; Wu, Jinshun; Xu, Peng (Elsevier, 2016)
This paper presents a real-time experimental measurement of a novel compact unglazed solar thermal facade (STF) system at outdoor environment in Shanghai, China for about a whole summer week. It demonstrates the daily average solar thermal efficiency fluctuated from 40% to 45.5%. The overall result indicates the advantages of the STF with simple structure, low cost and high feasibility in architectural design for energy-efficient building application, especially at future district or city levels.